E-118 Mechanical thrombectomy in distal vessels: revascularization rates, complications and functional outcome. (22nd July 2019) - Sweid, A; Head, J; Tjoumakaris, S; Xu, V; Shivashankar, K; Alexander, T; Gooch, M; Herial, N; Rosenwasser, R; Jabbour, P
Abstract : Background and importance: Pivotal trials have shown the tremendous efficacy of mechanical thrombectomy in proximal occlusions (PO). However distal occlusions (DO) involving M2 and beyond, distal ACA (A2) and posterior cerebral arteries were not represented. The thoughts are that distal vessels supply a smaller brain area, however, with significant symptoms paired with accessible occlusions, the concept may need to be revisited. In this study, we investigated the efficacy and safety of distal circulation mechanical thrombectomies compared to proximal circulation mechanical thrombectomies. Methods: A retrospective review of patients presenting with distal circulation acute ischemic stroke (AIS) who underwent mechanical thrombectomy at a tertiary referral center between 2010 and 2018. Results: Out of 453 patients who underwent mechanical thrombectomy for AIS, 73 patients had a DO (average age 72 years, 59% female). The mean NIHSS upon admission was 12 (95% CI: 11–14). The mean procedure time was 45 minutes (95% CI: 38–52) and mean time to revascularization, from symptom onset to finishing the thrombectomy procedure, was 522 minutes (95% CI: 438–5607). 45% (n=34) of subjects received tPA. Vessels involved included M2 (89%, n=68), A2 (3%, n=2), PCA (3%, n=2), and M3/4 (5%, n=4). A stentreiver alone was used in 11% of the cases (n=8), aspiration alone in 8% (n=6), and both stentreiver and aspiration in 72% (n=55), with failed attempts in 9% (n=7) of cases. Most procedures required one pass to recanalize the vessel (55%, n=42). TICI > 2b was achieved in 88% (n=67) of the subjects. Mean length of stay was eight days (95% CI: 6–10). Mortality was noted in 8% (n=6) of patients and independent functional outcome of mRS < 2 at three months was seen in 70.9% with clinical follow up. On univariate analysis peri-procedural distal emboli was significantly higher in DO group compared to PO group (7% vs. 2%, p<0.05) while post-procedural sICH was significantly lower in DO group compared to PO group (0% vs. 6%, p<0.05); vessel recanalization (TICI > 2b) was not significantly different between DO and PO. However, procedure time was significantly shorter in the DO group (45 min vs. 52 min, p=0.05) and the mean number of passes were lower in the DO group (1.5 vs. 1.8, p=0.01). Mortality rate and good functional outcome was not significantly different between both groups. On multivariate analysis, DO group had a significantly shorter length of stay by about two days, compared to PO, when controlling for confounders (coef: -2 days, 95%CI: -4 to 0 days, p=0.05). Subjects with PO were over five times more likely to have a good TICI score compared to DO group (OR: 5.69, 95% CI: 1.22–26.5, p<0.05). There was no significant difference in peri-procedural and post-procedural complications, a good functional outcome at three months, and mortality between both groups. Conclusion: Mechanical thrombectomy procedure for distal circulation strokes is as effective and safe as a proximal group. Though distal vessels supply smaller brain area, however when symptoms are pronounced the benefit of the procedure outweighs the risks. Disclosures: A. Sweid: None. J. Head: None. S. Tjoumakaris: None. V. Xu: None. K. Shivashankar: None. T. Alexander: None. M. Gooch: None. N. Herial: None. R. Rosenwasser: None. P. Jabbour: None.